Health and safety systems in Islam based on Quran and Islamic narrations - Gholamreza EsmHusseini; Javid Fereidouni (Health Science Monitor)
Background & Aims: One significant aspect of Islam's comprehensiveness is its health recommendations, which are vital for both worldly and spiritual well-being, as reflected in verses, traditions, and the lives of the Imams (PBUH). This research aims to elucidate the health system within Islamic teachings using a descriptive and library-based approach. Materials & Methods: The study begins by extracting health recommendations from Islamic texts, followed by an analysis through the lens of jurisprudence to outline the framework of Islamic health and wellness, including its goals, methods, and overarching principles. Results: The findings reveal that Quranic and religious teachings, along with rational and narrative foundations, emphasize the biological, behavioral, and cultural aspects of health. The research highlights the foundations, goals, dimensions, and cognitive, behavioral, and emotional strategies related to health in Islam, underscoring their systematic relationships with the health system through jurisprudential principles. Conclusion: It concludes that adherence to these principles significantly influences human behavior and lifestyle, ultimately affecting one's health and spiritual fulfillment in this life and the hereafter, thereby gaining the pleasure of God Almighty.